2019
DOI: 10.1038/s41431-019-0402-9
|View full text |Cite|
|
Sign up to set email alerts
|

Immunity and mental illness: findings from a Danish population-based immunogenetic study of seven psychiatric and neurodevelopmental disorders

Abstract: Human leukocyte antigen (HLA) genes encode proteins with important roles in the regulation of the immune system. Many studies have also implicated HLA genes in psychiatric and neurodevelopmental disorders. However, these studies usually focus on one disorder and/or on one HLA candidate gene, often with small samples. Here, we access a large dataset of 65,534 genotyped individuals consisting of controls (N = 19,645) and cases having one or more of autism spectrum disorder (N = 12,331), attention deficit hyperac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 46 publications
(42 reference statements)
1
57
0
Order By: Relevance
“…However, recent HLA haplotype-based analysis have identified both risk and protective HLA haplotypes regarding autism ( Bennabi et al, 2018 ): (i) the celiac disease-associated HLA-DRB*11∼DQB1*07 haplotype is associated with autism risk, especially in patients with high scores for social and non-verbal functioning, the two proxies of disease severity, as well as being parsimonious with the role of gastro-intestinal alterations in patients with autism ( Vuong and Hsiao, 2017 , Hughes et al, 2018 ), (ii) as in schizophrenia, a protective status is conferred by the HLA 8.1 AH, and as such expected to be associated with decreased complement C4 and synaptic pruning especially as cortical thickness abnormalities were amply documented in autism (Braden et al, 2019; Levman et al, 2019; Periera et al, 2018) along with an MRI-demonstrated decrease of cortical thickness ( Laidi et al, 2019 ), but raised levels of steady state pro-inflammatory activity; and iii) in a subset of patients with regressive autism, a subgroup known to have particularly pronounced immune dysfunctions, protection was afforded by a class II sub-haplotype, namely HLA-DPA1*01∼DPB1*04 (Tamouza et al, 2020). Of interest another HLA-DPB1 allele, namely DPB1*15:01 recently demonstrated to confers protection against intellectual disability and autism in a large survey from northern Europe ( Nudel et al, 2019 ). However, it is worthy to keep in mind that recent very large GWAS failed to detect MHC-linked signals ( Grove et al, 2019 ), a finding possibly reflecting disease heterogeneity and/or scarcity of post-GWAS HLA imputation studies in ASD.…”
Section: Hla Diversity and Common Major Psychiatric Disordersmentioning
confidence: 99%
“…However, recent HLA haplotype-based analysis have identified both risk and protective HLA haplotypes regarding autism ( Bennabi et al, 2018 ): (i) the celiac disease-associated HLA-DRB*11∼DQB1*07 haplotype is associated with autism risk, especially in patients with high scores for social and non-verbal functioning, the two proxies of disease severity, as well as being parsimonious with the role of gastro-intestinal alterations in patients with autism ( Vuong and Hsiao, 2017 , Hughes et al, 2018 ), (ii) as in schizophrenia, a protective status is conferred by the HLA 8.1 AH, and as such expected to be associated with decreased complement C4 and synaptic pruning especially as cortical thickness abnormalities were amply documented in autism (Braden et al, 2019; Levman et al, 2019; Periera et al, 2018) along with an MRI-demonstrated decrease of cortical thickness ( Laidi et al, 2019 ), but raised levels of steady state pro-inflammatory activity; and iii) in a subset of patients with regressive autism, a subgroup known to have particularly pronounced immune dysfunctions, protection was afforded by a class II sub-haplotype, namely HLA-DPA1*01∼DPB1*04 (Tamouza et al, 2020). Of interest another HLA-DPB1 allele, namely DPB1*15:01 recently demonstrated to confers protection against intellectual disability and autism in a large survey from northern Europe ( Nudel et al, 2019 ). However, it is worthy to keep in mind that recent very large GWAS failed to detect MHC-linked signals ( Grove et al, 2019 ), a finding possibly reflecting disease heterogeneity and/or scarcity of post-GWAS HLA imputation studies in ASD.…”
Section: Hla Diversity and Common Major Psychiatric Disordersmentioning
confidence: 99%
“…For example, CNTNAP2 has been highlighted in studies of autism spectrum disorder (ASD) [Alarcon et al, ] and attention deficit/hyperactivity disorder (ADHD) [Elia et al, ], and rare variants in CNTNAP2 were found in children with childhood apraxia of speech [Worthey et al, ]; CMIP has been implicated in ASD [Van der Aa et al, ]; ATP2C2 has been implicated in ADHD [Lesch et al, ]. HLA genes have been implicated in ASD and ADHD as well [Lee et al, ; Nudel et al, ; Odell, Warren, Warren, Burger, & Maciulis, ; Torres, Maciulis, Stubbs, Cutler, & Odell, ; Torres et al, ; Wang et al, ; Warren et al, ]. In addition to the genetic overlaps between ASD, ADHD, and SLI, it is known that language and communication may be impaired in ASD [Dover & Le Couteur, ] and ADHD [Baird, Stevenson, & Williams, ].…”
Section: Introductionmentioning
confidence: 99%
“…Because whole blood is being profiled, one must be cautious about an over-representation of immune-related transcripts (which are very plentiful in whole blood), but conversely, one cannot dismiss immune involvement as noted earlier. The potential role of inflammatory factors in ADHD has been raised over the years and is supported by various circumstantial data as recently reviewed [ 32 ], and recent analysis suggests the potential role of HLA loci in neurodevelopmental disorders such as ASD, and to a lesser degree ADHD [ 52 ].…”
Section: Resultsmentioning
confidence: 99%